Resistencias: hacia una poética del espacio cortés: el Roman de Troie - Valero Moreno, Juan Miguel (Troianalexandrina, 2011)
Abstract The following essay attempts, using the tools of literary history, hermeneutics and phenomonology, to explore the poetics of courtly space in medieval Romance literature. Thus, the Benoît de Sainte-Maure's Roman de Troie is taken as a model, since it subsists as a cornerstone within the literary and iconographic tradition of the theme of the City of Troy, stretching between Antiquity and the end of the Middle Ages. In particular, we delineate how the urban space of Troy in Benoît's work is constituted through a rewriting and reimagining of the Heavenly Jerusalem of Revelation, whose meaning affects the reading of the poem as a whole. Outside the verse Roman de Troie this form of reading is unproductive, and the symbolic space created by Benoît is trammelled by the